Integration of Sustainability Literacy in Digital Learning in Chemistry Education: A review - Refmidawati; Megahati S, Ruth Rize Paas (RADINKA JAYA UTAMA PUBLISHER, 2023)
Giving students the knowledge and skills they need to support sustainable development is one way that sustainability literacy is being promoted. To enhance the material on sustainability literacy, this article maps perspectives on sustainability literacy and the relationship between the Education for Sustainable Development (ESD) idea and chemistry education. The study's objectives are to: (1) map out the body of research on sustainability literacy; and (2) examine how the ESD idea relates to chemistry education to promote sustainability literacy. According to Kitchenham, the approach is Review. 31 international journals published between 2012 and 2023 were the sources of the papers used; they were retrieved from the Google Scholar database and Scopus-indexed. The study's findings demonstrate the widespread applicability of sustainability literacy across a range of scientific domains and application foci. Many well-researched ESD implementation approaches in chemistry education might serve as a guide when creating ESD in the classroom. An overview of the content of sustainability literacy that is pertinent to chemistry education as well as how it may be applied to different learning domains is given in this paper. It also offers perspectives for scientists, chemical instructors, and ESD developers.